Legal Governance Failures in Environmental Supervision: A Constitutional Analysis of Flash Flood Disasters in Indonesia - Aslan Noor; Jaenal Abidin; Andika Kharisma; Rosi Liandani (Fakultas Syariah INSURI Ponorogo, 2026)
The November 2025 hydrometeorological disaster in Aceh, North Sumatra, and West Sumatra, which caused approximately 800 fatalities and displaced hundreds of thousands of residents, raises a fundamental constitutional question: whether the disaster resulted from natural forces or systemic governance failure. This normative legal research examines that question through legislative, conceptual, and case-based approaches, analyzing Law No. 32 of 2009 on Environmental Protection and Management, Law No. 41 of 1999 on Forestry, and Law No. 18 of 2013 on Forest Destruction Prevention. The research identifies a tripartite governance failure: permissive licensing that authorized ecologically destructive activities in upstream watersheds, supervisory fragmentation that prevented timely regulatory intervention, and reactive enforcement oriented toward administrative sanction rather than ecological restoration. This research makes a distinct theoretical contribution by reframing governance-driven ecological disasters as constitutional accountability failures under Article 28H paragraph (1) of the 1945 Constitution, rather than as mere administrative irregularities, thereby elevating the standard of the institutional remedy required. The research recommends restructuring the AMDAL instrument, clarifying inter-institutional supervisory jurisdiction to operationalize accountability under Article 112, and mandating restorative obligations as legally enforceable consequences of environmental harm.